EDUCATION ON PREVENTING TRAPEZIUS MUSCLE PAIN CAUSEDBY THE USE OF TOTE BAGS AMONG STUDENTS: EDUKASI PENCEGAHAN NYERI OTOT TRAPEZIUS AKIBATPENGGUNAAN TOTEBAG PADA SISWA - Silvia Okta Ardono; Artanti Nariswari; Elvyra Rahma Anggraeni; Tahtya Triatmarchge Zabrina; Mufti Aliyul Mughni; Arshy Prodyanatasari (PT. ROCE WISDOM ACEH, 2026)
The use of tote bags among teenagers has become increasingly common, and carrying them on oneshoulder may cause tension in the trapezius muscle, potentially leading to discomfort. This conditionemphasizes the need for proper education regarding the risks and how to prevent them. This community service activity aimed to evaluate the effectiveness of an educational intervention in increasing students’ knowledge about preventing trapezius muscle pain related to tote bag use. A pre-experimental one-group pretest–posttest design was applied, involving 25 students from Kediri 6 Public High School. The intervention consisted of health education delivered through leaflets and a demonstration of trapezius stretching. Data were collected using a 12-item pretest and posttest questionnaire. Descriptive statistics and the Wilcoxon Signed Rank Test were used to analyze changes in knowledge scores. The results showed an increase in the mean score from 64.48 on the pretest to 87.20 on the posttest. The Wilcoxon test indicated a significant improvement in knowledge (p = 0.000, p < 0.05). These findings demonstrate that the educational intervention was effective in enhancing students’ understanding of the risks of tote bag use and ways to prevent trapezius muscle pain. It is recommended that similar programs be implemented periodically in schools to promote awareness of musculoskeletal health.